2023
DOI: 10.7554/elife.85494
|View full text |Cite
|
Sign up to set email alerts
|

Transferred mitochondria accumulate reactive oxygen species, promoting proliferation

Abstract: Recent studies reveal that lateral mitochondrial transfer, the movement of mitochondria from one cell to another, can affect cellular and tissue homeostasis1,2. Most of what we know about mitochondrial transfer stems from bulk cell studies and have led to the paradigm that functional transferred mitochondria restore bioenergetics and revitalize cellular functions to recipient cells with damaged or non-functional mitochondrial networks3. However, we show that mitochondrial transfer also occurs between cells wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Although we enhanced mitochondrial mass in CD4 + T cells, we would not anticipate functional improvements if dysfunctional mitochondria were transferred. Studies examining the impact of intercellular mito-transfer, modulated by tube-nano-tunnels [80], and engulfment of dysfunctional mitochondria [81], demonstrate that immune cell function worsened [80, 81]. This reinforces that the quality of donated mitochondria is equally important in the mitochondrial mass dependent plasticity of aged CD4 + T cells and other immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although we enhanced mitochondrial mass in CD4 + T cells, we would not anticipate functional improvements if dysfunctional mitochondria were transferred. Studies examining the impact of intercellular mito-transfer, modulated by tube-nano-tunnels [80], and engulfment of dysfunctional mitochondria [81], demonstrate that immune cell function worsened [80, 81]. This reinforces that the quality of donated mitochondria is equally important in the mitochondrial mass dependent plasticity of aged CD4 + T cells and other immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the co-culture experiment, we observed only unidirectional transfer of toxic fragmented mitochondria to their neighbouring cells. Several studies have shown that accumulated ROS with transferred toxic mitochondria could facilitate cell proliferation (Heinke, 2022, Kidwell, Casalini et al, 2023. The observations suggest that astrocytes and astroglia cells share their toxic organelles (lysosomes and mitochondria) with surrounding neighbours to dilute the toxic burden, and the transferred toxic mitochondria may contribute to facilitating proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…If material transfer occurs and is a biologically important process remains to be determined. However, it is worth noting that intercellular transfer from photoreceptors to Müller glia (Hutto et al, 2023), and from macrophages to other cells (Kidwell et al, 2023; Roh-Johnson et al, 2017), have been documented. Nonetheless, the observations from our recordings support that both a “strong-armed” approach by microglia, in which microglia outcompete Müller glia for the apoptotic cell to pull it away, may be possible in addition to a coordinated process in which one or both cells execute a regulated signaling process for the exchange of the YFP+ cells, both of which are yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%